Effect on OPU/IVEP success of different applications for synchronizing follicular waves prior to superstimulation in holstein heifers - M. F. Çiftçi; Ö. F. Yeşilkaya; S. Ü. Çizmeci; M. Gölbaşı; A. Sarı; D. A. Dinç (Archives Animal Breeding)
The aim of this study is to determine the effects of different treatments used to synchronize follicular waves prior to superstimulation of responses and in vitro embryo production (IVEP). The study used 12 healthy Holstein heifers. In GnRH + P4, an intravaginal progesterone (P4) device was inserted into the vagina on a random day of the estrous cycle, and 10 µg of the gonadotropin-releasing hormone (GnRH) was administered intramuscularly at the same time. After these applications, 25 mg of PGF2α was administered intramuscularly on the third and fourth days of treatment. The intravaginal progesterone device was removed on day 5. At the same time, 125 µg of follicle-stimulating hormone (FSH) was administered intramuscularly as a single dose. Two days after the FSH injection, oocytes were retrieved using transvaginal ultrasound. In contrast to GnRH + P4, hCG + P4 was performed with 1500 IU hCG (human chorionic gonadotropin) injection instead of GnRH. In DFR + P4, dominant follicles were removed. In the control group, the oocytes were collected on a random day of the estrous cycle. The ovarian follicles were measured by ultrasound prior to oocyte collection. The number of medium-diameter follicles (3–8 mm) was found to be greater in hCG + P4 and DFR + P4 than in the control group (p<0.05). It was determined that the numbers of viable oocytes, Grade A oocytes, cleaved oocytes, and blastocysts obtained per ovum pickup (OPU) were greater in hCG + P4 and DFR + P4 than in the control group (p<0.05). In addition, the numbers of Grade A oocytes and blastocysts obtained per OPU were greater in the DFR + P4 group than in the GnRH + P4 group (p<0.05). As a result, it was thought that synchronization of follicular wave emergence with DFR and hCG in the short synchronization protocols used before superstimulation could increase the success rate of OPU/IVEP programs.